PENGARUH KEMAMPUAN KERJA, KOMITMEN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI - Muhridin Muhridin; Ansir Ansir; Sinarwaty Sinarwaty (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
The objective of this research was to examine the effect of Work Capability, Work Commitment and Job Satisfaction on employee performance at Wakatobi Regency Office of Public Works and Spatial Planning. The population in this research were all Civil Servants of the Office of Public Works and Spatial Planning of Wakatobi Regency, amounting 41 people. Because of the small population, in this research the population was also used as a whole sample or census. Therefore, the number of samples used in this study was 41 people. Data was collected through questionnaires and interviews, while the research instrument was using Likert scale (5 points). The collected data then was analyzed using multiple linear regression analysis. The result of this research indicates that work capability, organization commitment, and job satisfaction have positive and significant effect on employee performance at the Office of Public Works and Spatial Planning in Wakatobi Regency, both simultaneously and partially. This means that if work capability, organization commitment and job satisfaction improve, it will improve employee performance, and vice versa if work capability, organization commitment, and job satisfaction degrade, it will degrade employee performance..Keywords: work capability, work commitment and job satisfaction on employee performance